First adult record of the barracudina Lestidiops extremus (Ege, 1953), based on a specimen from the Philippines (Teleostei: Paralepididae) - Ho, Hsuan-Ching; Huang, Chih-Hsiung (Zootaxa, 2022)
The adult morphology of Lestidiops extremus (Ege, 1953), a barracudina originally described based on postlarvae from Indonesia, has long been a mystery. An adult specimen collected from off the Philippines represents the first confirmed record of an adult of this species. Observations on the holotype and a detailed description of the adult are provided. The location of the pelvic-fin origin in the adult, clearly behind the posterior end of the dorsal-fin base, is unique within this genus and the entire subfamily Lestidiinae. The present find extends the known range of the species from northwestern New Guinea, Indonesia, to seas east of the Philippines.